THE ROLE OF ISLAMIC FINANCIAL INCLUSION IN ENHANCING SOCIAL WELFARE AND REDUCING ECONOMIC INEQUALITY IN INDONESIA: A LITERATURE REVIEW - RIFKI FAUZI; Noviana Aulia; Midza Safiyra Zahra; Khairunnisa Putri Liestiyanto; Muhammad Ghaly Mumtaz (PT. Samudra Solusi Profesional, 2026)
Economic inequality remains a significant challenge in Indonesia despite various developmental efforts. This study aims to examine the role of Islamic financial inclusion in improving community welfare and reducing economic disparity. Using a systematic literature review approach, this paper analyzes data and existing research from the Financial Services Authority (OJK), Bank Indonesia (BI), and Central Bureau of Statistics (BPS), alongside scholarly articles. The findings indicate that Islamic financial inclusion, driven by the expansion of Islamic banking and Sharia fintech, provides equitable access to capital, particularly for Micro, Small, and Medium Enterprises (MSMEs). By adhering to the principles of Maqashid Sharia and distributive justice, Islamic financial inclusion not only mitigates poverty but also fosters sustainable economic empowerment. The study concludes that collaborative stakeholder strategies are essential to accelerate Sharia financial literacy and inclusion, ultimately driving broader national economic welfare